Pengaruh Kebiasaan Belajar dan Sikap Siswa Terhadap Hasil Belajar Matematika - Eleonora Dwi w; Lydia Arfani Suangga; Ibnu Sina (Universitas Pancasakti Tegal, 2021)
This study aims to describe the influence of students' learning habits and attitudes in the mathematics learning process. The purpose of this study was to prove how the influence of students' learning habits and attitudes on mathematics learning outcomes. This study uses a quantitative approach with the Expos t facto method. Data collection techniques used are interviews, documentation, and questionnaires. To find out the results of learning mathematics and questionnaires using a Likert scale 4 for data on students' learning habits and attitudes. The research data were then analyzed using simple regression and multiple regression. The results showed that there was an influence between study habits and students' attitudes towards mathematics learning outcomes.